RENCANA AKSI NASIONAL BELA NEGARA - Agus Subagyo (Universitas Jenderal Ahmad Yani, 2019)
This article aims to explain the 2018-2019 state defense action plan in Presidential Instruction No. 7 of 2018 which mandates all ministries, non-ministerial government agencies, and local governments to take action to defend the country through three stages, namely the stages of socialization, internalization, and movement action. The dilution of the state defense action plan at the central government level has been very active, however, at the level of the reverent regional government it has not yet been felt, especially with the existence of regional autonomy where the central government is not necessarily able to